SENSITIVITY ANALYSIS IN THE HEAT TRANSFER IN A FINNED NUCLEAR FUEL ELEMENT - Tito, M. W. C.; Lira, C. A. B. O.; Lima, F. R. A.; Baliño, J. L. (Revista de Engenharia Térmica, 2004)
To carry out sensitivity analysis on a finned surface, the differential perturbative method is applied in a heat conduction problem within a thermal system, made up of a onedimensional circumferential fin on a nuclear fuel element. The model is described by the temperature distribution equation and the further specific boundary conditions. The adjoint system is used to determine the sensitivity coefficients for the case of interest. Both, the direct model and the resultant equations of the perturbative formalism are solved. The convective heat flow rate of the fin and the average excess temperature were the response functionals studied. The half thickness, the thermal conductivity and heat transfer coefficients, and the excess temperature at the base of the fin were the parameters of interest for the sensitivity analysis. The results obtained through the perturbative method and the direct variation had, in a general form and within acceptable physical limits, good concordance and excellent representativeness for the analyzed cases. It evidences that the differential formalism is an important tool for the sensitivity analysis and also it validates the application of the methodology in heat transmission problems on extended surfaces. The method proves to be necessary and efficient while elaborating thermal engineering projects.